Memo from Melvin M. Vuksich regarding supplementary agreements for JSU ROTC, April 1965 - Vuksich, Melvin M. (JSU Digital Commons, 1965)
Memo from Melvin M. Vuksich, US Army Headquarters, Fort McPherson, GA, regarding supplementary agreements for the JSU ROTC. Enclosed are the signed agreement from March 1965 detailing facilities for the ROTC (the former Jacksonville High School building) and a campus map. (memo dated April 6, 1965) https://digitalcommons.jsu.edu/rotc_docs/1010/thumbnail.jpg